PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN KOMPETENSI GURU DIMEDIASI OLEH KEPUASAN KERJA GURU TERHADAP KINERJA GURU SD SEKECAMATAN SAYUNG KABUPATEN DEMAK (Students' Journal of Economic and Management, 2012)
This study aimed to analyze the influence of principal leadership and teacher competence on teacher performance in elementary schools at Dindikpora Sub District Sayung at Demak Regency moderated by job satisfaction. In this study population was 343 people, while the sample as many as 78 respondents with Slovin method. Measurements using a Likert scale of 7 (seven) alternative answers. Test instruments used are validity and reliability. While the test model used is the coefficient of determination and F test (Goodness of Fit). Testing this hypothesis in this study using regression analysis. Based on the study can be summarized as follows: (i) the principal leadership a significant effect on and job satisfaction of teachers and not significant for performance. (Ii) the competence of teachers significantly influence the performance of teachers and teachers job satisfaction. (iii). Job satisfaction mediates the effect of principal leadership on teacher performance (iv) job satisfaction did not mediate the effect of teacher competence on teacher performance. Keywords: principal leadership, teacher competence, teacher job satisfaction, teacher performance.